(untitled) (Journal of the College of Basic Education, 2022)
The present study was Conducted to evaluate the effect of amixture of three species of arbuscular mycorrhizal fungi ( Glomus etunicatum , G. leptotichum and Rhizophagus intraradices ) in inducing the non-enzymatic antioxidants of tomato roots infected with Fusarium oxysporum f.sp. Lycopersici wich cause Fusarial wilt disease , and planted for 10 weeks in the presence of the organic matter ( peatmose) , using pot cultures in aplastic green house , Results indicated significant reduction of disease incidence percentage and infection rate of roots infected with the pathogen 4 weaks after mycorrhizal colonization in all treatments ( single , dual and trial interactions) . on the other hand mycorrhizal colonization of the roots in the presence of organic matter and pathogen after 4 weaks of pathogen infection resulted in significant increase of proline content, total phenol , malondialdehyde , glutathione and hydrogen peroxide of roots in all treatment ( single , dual and trial interaction ) . The trial treatment ( M ×F.o.l .×O) Showed the highest content of all antioxidants tested followed by the dual ( M ×F.o.l .) , whereas the lowest content of all antioxidants for all treatments was shown at the time of plantation ( OW+ ) in the presence of the pathogen